Correction: Electrochemical and electrocatalytic reaction characteristics of boron-incorporated graphene via a simple spin-on dopant process. Issue 17 (18th April 2018) - Jang, A.-Rang; Lee, Young-Woo; Lee, Sang-Seok; Hong, John; Beak, Seong-Ho; Pak, Sangyeon; Lee, Juwon; Shin, Hyeon Suk; Ahn, Docheon; Hong, Woong-Ki; Cha, SeungNam; Sohn, Jung Inn; et al.
Abstract : Correction for 'Electrochemical and electrocatalytic reaction characteristics of boron-incorporated graphene via a simple spin-on dopant process' by A-Rang Jang et al., J. Mater. Chem. A, 2018, DOI: ;10.1039/c7ta09517a .